Comprehensive 3D CT Imaging of Horseshoe Kidney with Anatomical Details - Kaushik Bhattacharya; Aarzoo Nagpal; Prabhdeep Singh Chowdhary; Jaspreet Singh Bedi; Rakhi Kumari (National Board of Examinations Journal of Medical Sciences, 2025)
A 3D CT scan should be the investigation of choice in case of congenital anomalies like Horseshoe kidney, as it guides the surgeon precisely before any major surgical intervention.